The Leader of Digital Transformation in The Post-Pandemic Era in The Context of Collaboration - Julia Anamaria ȘIȘU; Andrei Constantin TÎRNOVANU; Marian NĂSTASE (Communications of International Proceedings, 2022)
Solid theories claim that the future of every industry is a digital one. The current study aims to deepen the impact of leaders in the digital transformation process. Leaders are no longer only in the position of leading organizations, but also of following and co-creating with other companies. The collaboration between leaders and organizations to co-generate new capabilities on the market creates a new paradigm that supports cooperation, collaboration, and competition at the same time, without excluding any of the terms. Instead of dividing the market share between competing companies, a new concept of cooperation is emerging, which aims to increase the market's value and expand and widen it. Consumers appreciate most digital products and services more when integrated with competitors' solutions than by themselves. Thus, the concept of "complementors" is a precious one in the new market economy, being adopted by most of the technological giants.The scientific article presented contributes to the understanding of complements, through the relevant roles and contributions in a business ecosystem based on digitalization.
Keywords: Digital Leader; Transformative Leadership; Coopetition; Network Centric; Complements.